Italy : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2020)
This Financial System Stability Assessment paper on Italy highlights that substantial progress has been made in recent years in strengthening the financial sector, however, important weaknesses remain. Bank capitalization and asset quality have improved considerably but are still below the European Union average and the financial sector has large exposures to the Italian sovereign. The financial sector faces important vulnerabilities and a challenging baseline outlook. The sector is highly dependent on the European Central Bank's Targeted Longer-Term Refinancing Operations. Profitability is also still low, particularly in segments of small and mid-sized banks. This reflects in part weak economic growth in Italy over the past decade, as well as high structural operating costs, unsustainable business models and corporate governance weaknesses. Solvency stress tests indicate that many banks with material aggregate total asset share continue to be vulnerable to an adverse scenario. Efforts should focus on further enhancing banks' capitalization, operational efficiency, governance, and business models. Specifically, the authorities should consider more escalated corrective measures for weak banks, utilizing the full gamut of their toolkit, to ensure that banking sector weaknesses do not linger, and costs are contained.